Intranet working - Eckel, George (New Riders, 1996)
Intranet Working shows you how to implement and use a browser as a front end, replacing more expensive systems such as Lotus Notes or Microsoft Exchange. It explains how to implement email, improve efficiency via customized file exchange, and develop a local area network into a virtual data exchange - where information is easily exchanged through one convenient front end.